Blockchain-specific technological capability accumulation: the case of blockchain innovation projects in Petrobras - Castro, Henrique Ribeiro (2021)
This thesis explores the combination of existing non-blockchain-specific capabilities with internal and external learning mechanisms, to identify how latecomer firms develop their initial blockchain-specific technological capabilities to undertake innovation activities. Studies on firm-level capability-accumulation had ignored blockchain to this day, whereas most studies on this technology primarily focus on conceptual discussions or on technical specifications, generally not concerned with the necessary capabilities to transform their inventions into innovations. More importantly, such studies neglect technical and organizational dimensions of blockchain implementations, which are decisive to understand the different impacts in firms’ accumulation processes and innovation outputs. This study is based on interviews and archival data collected from Petrobras’ first two blockchain innovation projects and applied cross-case analysis methods to examine how distinct learning efforts affected blockchain-specific technological capability-accumulation. Overall, findings indicate that (i) non-blockchain-specific capabilities influence on external knowledge acquisition through alliance-making with suppliers and universities, and on internal knowledge creation, by integrating multidisciplinary skills available at Petrobras, which in turn, facilitated knowledge creation though search, experimentation, and codification internal mechanisms; (ii) learning linkages were important sources of external knowledge, acting as catalysts of initial accumulation, but had to be complemented by open-source codified knowledge and internal learning mechanism when knowledge gaps emerged; (iii) it was possible to observe team-level knowledge accumulation and distinct learning mechanisms between each project phases; and (iv) knowledge gaps were less frequent when external knowledge sources met the required capability levels in both technical and organizational blockchain dimensions. Finally, this study opens a research avenue for studies on blockchain-specific technological capability-accumulation, and has practical implications, by translating the experience from real-world blockchain projects.